2021
DOI: 10.1111/jgh.15432
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of acid suppressants for gastrointestinal bleeding prophylaxis in cardiac care unit patients

Abstract: Background and Aim: Concerns regarding adverse events associated with proton pump inhibitors (PPIs) and histamine-2 receptor antagonists (H2RAs) for gastrointestinal bleeding (GIB) prophylaxis in the intensive care unit have increased in recent years. Few studies have focused on acid suppressant use in the cardiac care unit (CCU) setting exclusively. We performed a cohort study to determine the efficacy and safety of acid suppressants for GIB prophylaxis in CCU patients. Methods: This retrospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[13][14][15] Although PPIs are considered relatively safe, some case-control studies suggest that their use may be associated with an increased risk of respiratory tract infections 7 and CAP in adults and children and even hospitalization for pneumonia. 16 However, the specific mechanism is still not fully elaborated, and the effect of PPIs on CAP is still controversial. Therefore, it is necessary to perform a metaanalysis to comprehensively and systematically understand the effect of PPIs on CAP.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Although PPIs are considered relatively safe, some case-control studies suggest that their use may be associated with an increased risk of respiratory tract infections 7 and CAP in adults and children and even hospitalization for pneumonia. 16 However, the specific mechanism is still not fully elaborated, and the effect of PPIs on CAP is still controversial. Therefore, it is necessary to perform a metaanalysis to comprehensively and systematically understand the effect of PPIs on CAP.…”
Section: Introductionmentioning
confidence: 99%
“…One large retrospective study described an increase in delirium in patients exposed to H2RAs or PPIs compared to controls who were not receiving either medication [12]. Some studies have shown an association between PPIs and infectious complications [13,14]. Pooled analyses, however, have been inconsistent [5 ▪ ,11 ▪ ,15].…”
Section: Medications Used For Stress Ulcer Prophylaxismentioning
confidence: 99%